Does Previous Experience with Online Platforms Matter? A Survey about Online Learning across Study Programs - Åse Nygren; Emil Alégroth; Anna Eriksson; Eva Pettersson (Education Sciences, 2023)
The COVID-19 pandemic has had a dramatic effect on society, including teaching within higher education that was forced to adapt to online teaching. Research on this phenomenon has looked at pedagogical methods as well as student perceptions of this way of teaching. However, to the best of our knowledge, no studies have looked at the wider perspective, within the entire student populous of a university, what students’ perceptions are and how these correlate with the students’ previous experiences and habits with online platforms, e.g., online streaming or social media. In this study, we perform a questionnaire survey with 431 responses with students from 20 programs at Blekinge Institute of technology. The survey responses are analyzed using descriptive statistics and qualitative analysis to draw its conclusions. Results show that there is no correlation between previous habits and student experience with online platforms in relation to online learning. Instead, other factors, e.g., teacher engagement, is found central for student learning and therefore important to consider for future research and development of online teaching methodologies.